STRATEGI GURU DALAM PEMBELAJARAN BERCERITA SISWA KELAS 4 DI SD NEGERI 2 SUMITA - Ni Komang Kembar Tri Dewi (LPPM Universitas Islam Darul `Ulum Lamongan, 2025)
This study aims to analyze the types of strategies and challenges encountered in storytelling instruction for fourth-grade students at SD Negeri 2 Sumita. This research uses a qualitative approach. The data collection methods and instruments used were observation and interviews. The study was conducted at SD Negeri 2 Sumita, with the research subjects being fourth-grade students and their classroom teacher. The results of the study show that: (1) the teacher implemented various storytelling strategies that were communicative, participatory, and interactive. The strategies included the use of visual media such as picture series and videos, small group discussions, practice sessions for storytelling in front of the class, and the provision of direct feedback on students' performances. Each lesson began with a clear explanation of the learning objectives, continued with core activities that actively involved students, and concluded with reinforcement and relevant follow-up assignments. These strategies proved effective in enhancing student participation, creativity, and confidence in oral storytelling; (2) the main challenges faced by the teacher included differences in students’ abilities to construct and deliver stories, lack of self-confidence among some students when speaking in front of the class, limited instructional time, and the lack of varied teaching media. Although strategies and media had been used optimally, these obstacles still hindered equitable learning outcomes. To address these issues, the teacher began to apply a gradual approach through small groups and planned to integrate more engaging digital learning technologies to better accommodate students' needs in a flexible and inclusive manner.